2016
DOI: 10.3892/ijmm.2016.2779
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping molecular pathways between cannabinoid receptors type 1 and 2 and estrogens/androgens on the periphery and their involvement in the pathogenesis of common diseases (Review)

Abstract: The physiological and pathophysiological roles of sex hormones have been well documented and the modulation of their effects is applicable in many current treatments. On the other hand, the physiological role of endocannabinoids is not yet clearly understood and the endocannabinoid system is considered a relatively new therapeutic target. The physiological association between sex hormones and cannabinoids has been investigated in several studies; however, its involvement in the pathophysiology of common human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 105 publications
0
17
0
Order By: Relevance
“… 19 Studies have also shown that activation of the CB 1 receptor also leads to regulation of mitogen-activated protein kinases (MAPKs) that are vital to inflammatory and immune cellular responses, including extracellular signal-regulated protein kinase 1/2 (ERK1/2), p38, and c-jun terminal kinase (JNK). 20 , 21 The phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) is a third pathway involved in cell growth and survival that may also be activated by CB 1 receptor. 22 , 23 Similarly, CB 2 receptor agonism modulates and inhibits AC and cAMP leading to the inactivation of PKA by G i/o protein coupling.…”
Section: Cb 1 and Cb 2 Receptormentioning
confidence: 99%
“… 19 Studies have also shown that activation of the CB 1 receptor also leads to regulation of mitogen-activated protein kinases (MAPKs) that are vital to inflammatory and immune cellular responses, including extracellular signal-regulated protein kinase 1/2 (ERK1/2), p38, and c-jun terminal kinase (JNK). 20 , 21 The phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) is a third pathway involved in cell growth and survival that may also be activated by CB 1 receptor. 22 , 23 Similarly, CB 2 receptor agonism modulates and inhibits AC and cAMP leading to the inactivation of PKA by G i/o protein coupling.…”
Section: Cb 1 and Cb 2 Receptormentioning
confidence: 99%
“…There is evidence that molecular pathways between CBRs and estrogens overlap, and this could impact pathogenesis of common diseases, including HR+ BC [38]. Most of the preclinical studies have explored the effects of cannabinoids on BC cell lines.…”
Section: Cannabinoids and Hormone Receptor-positive Breast Cancer (Prmentioning
confidence: 99%
“…Their pharmacological effects have been found to be mediated mainly through two specific plasma membrane G-protein-coupled receptors, referred to as cannabinoid receptors CB1 and CB2. Today, more receptors of the endocannabinoid system are known, including GPR55, GPR119 and TRPV1, however their physiological functions are still mostly unknown 12 16 . In addition it is widely accepted today that different cannabinoids act on multiple targets 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%